Heteronomy of architecture and design: the teaching of Gio Ponti - Bagnato, Vincenzo Paolo; Labalestra, Antonio (TECHNE - Journal of Technology for Architecture and Environment, 2021)
The celebration of the fortieth anniversary of Gio Ponti’s death offers the opportunity for in-depth study of his figure, and for renewed reflection on the whole Italian and international architectural culture. In this context, visions and ideas about modernity by the Milan architect appear emblematic and topical in relationship with the ever-changing socio-cultural conditions of our time. The new paradigm of design culture, with special reference to technology and industrial design, rediscover in Ponti’s figure important lessons concerning the even more heteronymous and hybrid condition of architecture, as long as they show a still possible synthesis between urban, architectural and design scale.